2002
DOI: 10.1017/s003382220006478x
|View full text |Cite
|
Sign up to set email alerts
|

Ingeis Radiocarbon Laboratory Dates IV

Abstract: We present here the results of dating of 80 archaeological and paleoenvironmental samples from Argentina and Uruguay, processed between 1986 and 1988 by M A Albero and M A Gonzalez. Series of samples and single samples are grouped by province and then by locality or archeological site, from north to south. See sample location maps for details.Procedures for sample pretreatment, counting, statistical analysis, and age calculation were essentially the same as previously described by Albero and Angiolini (1985). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
1
0
5
Order By: Relevance
“…En el año 1978, Jorge Fernández realizó la primera campaña de excavaciones en el sitio, en conjunto con Juan Schobinger, Rafael Goñi, Marta Ruiz y Carlos Baied. Como producto de estos trabajos pioneros se realizó una fecha radiocarbónica sobre materia orgánica de procedencia actualmente desconocida, la cual arrojó una edad de 11.150 ± 230 años 14 C AP (Cordero et al 2002). Aunque se carece de información contextual publicada, esta muestra indicó la presencia de sedimentos estratificados correspondientes al Pleistoceno tardío.…”
Section: Holoceno Tardío?unclassified
“…En el año 1978, Jorge Fernández realizó la primera campaña de excavaciones en el sitio, en conjunto con Juan Schobinger, Rafael Goñi, Marta Ruiz y Carlos Baied. Como producto de estos trabajos pioneros se realizó una fecha radiocarbónica sobre materia orgánica de procedencia actualmente desconocida, la cual arrojó una edad de 11.150 ± 230 años 14 C AP (Cordero et al 2002). Aunque se carece de información contextual publicada, esta muestra indicó la presencia de sedimentos estratificados correspondientes al Pleistoceno tardío.…”
Section: Holoceno Tardío?unclassified
“…Argentinean archaeologist Jorge Fernandez tested CHI in 1978, obtaining a 14 C age of 11,150 ± 230 B .P. for a sample of unknown composition and provenience (Cordero et al 2002). The presence of late Pleistocene deposits and signs of recent human impact suggested that further sampling would be useful for exploring early human colonization of Patagonia (Barberena etal.2010).…”
Section: A)mentioning
confidence: 99%
“…Décadas después, gracias a las anotaciones de campo de Goñi y a documentación fotográfica complementaria, fue posible identificar la ubicación aproximada de al menos dos cuadrículas excavadas por los tres últimos investigadores a partir de los motivos rupestres presentes en las fotos. Producto de estos trabajos pioneros se realizó un fechado radiocarbónico sobre materia orgánica de procedencia actualmente desconocida, que arrojó una edad de 11.150±230 años 14 C AP (Cordero et al, 2002). Aunque se carece de información contextual publicada sobre esta muestra, al menos indicó la presencia de sedimentos estratificados correspondientes al Pleistoceno Tardío.…”
Section: Antecedentes De Investigaciónunclassified